COMPARTMENT SYNDROME AS A CONSEQUENCE OF FIREARM INJURIES - Valentyna Chorna; Lyudmyla Hudzevych; Marina Zarichniuk; Iryna Korol (Scientific Journal of Polonia University, 2024)
At present, the problem of compartment syndrome remains relevant due to military actions in Ukraine. The pathogenesis of this syndrome lies in the increase of subfascial pressure in the osteofascial compartment, which disrupts innervation and blood supply. Along with this, muscle swelling of up to 30–50% occurs, causing additional pressure and complications. Compartment syndrome in the case of firearm injuries of the limbs occurs in 55.0% – fractures of the tibia, 39.0% – femur, 3.4% – forearm, 3.4% – foot bones. Since the beginning of the war in the east in 2014, the frequency of firearm injuries to the limbs has been 65.0% compared to torso injuries up to 20%. Delayed diagnosis or treatment of compartment syndrome can lead to disability, as irreversible nerve damage and muscle atrophy occur, with a mortality rate of about 50%. Also, with untimely assistance, the frequency of limb amputations is about half of the cases. The main and effective method of treatment is fasciotomy, but it also has certain complications with incorrect or delayed treatment. For example, the execution of fasciotomy with violations: 31.0% – fasciotomy of only one compartment of the affected segment, 27.0% – fasciotomy that did not have a decompressive effect, and others. To reduce complications including the formation of ischemic contracture (acute period – reactive-restored, residual period); neurodystrophic disorders; pseudarthrosis, osteomyelitis; delayed fracture consolidation, formation of pseudoarthrosis; patient death, timely diagnosis of compartment syndrome using magnetic resonance imaging, ultrasound, etc., is necessary. In our study, 3 clinical cases of compartment syndrome of the limbs with successfully performed fasciotomy are presented. As a result, patients have a positive prognosis due to timely diagnosis and treatment.